Evolutionarily Selected Overexpression of the Cytokine BAFF Enhances Mucosal Immune Response Against P. falciparum - Lodde, Valeria; Floris, Matteo; Beerman, Isabel; Munk, Rachel; Guha, Rajan; Steri, Maristella; Orrù, Valeria; Abdelmohsen, Kotb; Crompton, Peter D.; Gorospe, Myriam; Idda, Maria Laura; Cucca, Francesco (Frontiers in Immunology, 2020)
We have previously shown that a variant of the TNFSF13B gene that we called BAFF-var increases the production of the cytokine BAFF, upregulating humoral immunity and increasing the risk for certain autoimmune diseases. In addition, genetic population signatures revealed that BAFF-var was evolutionarily advantageous, most likely by increasing resistance to malaria infection, which is a prime candidate for selective pressure. To evaluate whether the increased soluble BAFF (sBAFF) production confers protection, we experimentally assessed the role of BAFF-var in response to malaria antigens. Lysates of erythrocytes infected with Plasmodium falciparum (iRBCs) or left uninfected (uRBCs, control) were used to treat peripheral blood mononuclear cells (PBMCs) with distinct BAFF genotypes. The PBMCs purified from BAFF-var donors and treated with iRBCs showed different levels of specific cells, immunoglobulins, and cytokines as compared with BAFF-WT. In particular, a relevant differential effect on mucosal immunity B subpopulations have been observed. These findings point to specific immune cells and molecules through which the evolutionary selected BAFF-var may have improved fitness during P. falciparum infection.